The Experience of Rev. Thomas H. Jones, Who Was a Slave for Forty-Three Years : Written by a Friend, as Related to Him by Brother Jones - Jones, Howard, 1940- (Book collections on Project MUSE., 2010)
In an examination of Union and Confederate foreign relations during the Civil War from both European and American perspectives, Jones explores a number of themes, including the international economic and political dimensions of the war, the North's attempts to block the South from winning foreign recognition as a nation, Napoleon III's meddling in the war and his attempt to restore French power in the New World, and the inability of Europeans to understand the interrelated nature of slavery and union.